Genetic structure and diversity of the seagrass Zostera marina along a steep environmental gradient, with implications for genetic monitoring - Ries, Stefanie R.; Faust, Ellika; Johannesson, Kerstin; Jonsson, Per R.; Moksnes, Per-Olav; Pereyra, Ricardo T.; Jahnke, Marlene (Frontiers in Climate, 2023)
Zostera marina (eelgrass) is a foundation species in coastal zones in the northern hemisphere declining across its distribution, which will likely accelerate under climate change. The Swedish coastline extends from the North Sea into the Baltic Sea and presents a distinctive research opportunity into an exceptionally steep salinity gradient, ranging from 26 to 5 psu, and an abrupt salinity shift in the entrance to the Baltic Sea. Genetic variation is an important component for potential persistence and adaptation of any species in a changing environment. To investigate coast-wide genetic variation and population structure of eelgrass, we assessed 15 eelgrass meadows along the Swedish east and west coasts with 2 138 single nucleotide polymorphisms (SNPs). Eelgrass population structure showed clear geographic structuring with genetic clines from west to east and parallel to the salinity gradient, as well as a genetic break at the entrance to the Baltic Sea. Eelgrass on the west coast had less clonality, higher genetic variation, and showed population differentiation on smaller geographic scales. In contrast, there was little genetic differentiation along the east coast, clonal reproduction was frequent, and three meadows were completely clonal. The dominance of a few or a single local clone and the resulting decrease in genetic variation will likely negatively affect the long-term persistence of eelgrass meadows, particularly in a changing climate. In addition, the lack of sexual reproduction renders Baltic eelgrass less likely to recover and recolonize after disturbance, and more difficult to restore. The here provided information on genetic clusters, clonality, and genetic variation can be included for prioritizing meadows for conservation, and for identifying meadows for restoration purposes. Moreover, this first genetic assessment of the Swedish coastline can serve as a baseline for temporal genetic monitoring of Swedish eelgrass populations.